Answer:41 − 45; 46 − 50; 51 − 55; 56 − 60
Step-by-step explanation:
Step-by-step explanation:
Well if you dont understand something ask a teacher for help or study on a topic that you struggle with for example math try looking up different math questions and solving them or ask a teacher is you can have pratice questions or problems then show it to him/her so they can check to see if you are right. Hope that help unless you dont understand a certain question that I might have missed.
Answer:
0
Step-by-step explanation:
Write out the 2 equations:
2x + y = -3
-2y = 6+4x
-You then pick a variable that you want to solve for. I chose to solve for y because it would be a bit easier.
-2y = 6 + 4x
-Divide both sides by -2 to isolate the variable
(-2y) / -2 = (6 + 4x) / -2
-it comes out to y = -3 -2x
-Now that you have the y you can plug in the value into the second equation.
2x + y = -3 ---> 2x + (-3 -2x) = -3
This can be simplified to:
2x - 3 - 2x = -3
The 2x's cancel out because there is a +2x and a -2x. You are left with a
-3 = -3. If you add 3 to both sides of the equation you end up with 0 = 0, which can be simplified to just 0.
To qualify as a polynomial, the expression in question:
* Consists of one or more terms * Variables are only with positive whole exponents* No variables in the denominator of any term (the coefficients however, can be fractions.)In that case the answer is most likely: